2009
DOI: 10.1097/ccm.0b013e31819ffe6d
|View full text |Cite
|
Sign up to set email alerts
|

The effect of daily bathing with chlorhexidine on the acquisition of methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus, and healthcare-associated bloodstream infections: Results of a quasi-experimental multicenter trial*

Abstract: We conclude that daily chlorhexidine bathing among ICU patients may reduce the acquisition of MRSA and VRE. The approach is simple to implement and inexpensive and may be an important adjunctive intervention to barrier precautions to reduce acquisition of VRE and MRSA and the subsequent development of healthcare-associated BSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
188
1
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(202 citation statements)
references
References 34 publications
5
188
1
5
Order By: Relevance
“…Chlorhexidine gluconate has been shown to be effective in reducing the risk of infection compared with standard washes and other antiseptic methods in a variety of medical specialties when applied after invasive procedures [3]. As such, a retrospective study by Farber et al [10] evaluated a total of 3715 patients using a similar chlorhexidine cloth protocol and showed contrasting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorhexidine gluconate has been shown to be effective in reducing the risk of infection compared with standard washes and other antiseptic methods in a variety of medical specialties when applied after invasive procedures [3]. As such, a retrospective study by Farber et al [10] evaluated a total of 3715 patients using a similar chlorhexidine cloth protocol and showed contrasting results.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors used a single application the morning of surgery, whereas our study used two applications, one the morning of and the second the evening before surgery. The potential benefit of the two-part application could have been demonstrated to be the result of a cumulative effect whereby there was a higher bactericidal cutaneous concentration [3]. Additionally, the superior protection against infection could have also been attributed to the rapid and residual bactericidal effects of chlorhexidine [13].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that a whole-body bath with an antiseptic agent reduces the bacterial load in the skin and lowers the risk of developing SSI (32)(33)(34)(35). According to the CDC, SSIs are the second most common cause of nosocomial infections and are responsible for more than 25% of hospitalrelated infections in the United States (36,37).…”
Section: Cleansing)mentioning
confidence: 99%
“…1 In addition to reducing HA-BSI, this strategy has also been shown to significantly reduce the transmission (acquisition) of multi-drug-resistant organisms (MDRO) in the ICU setting. 2,3 By contrast, much less data is available on this issue for patients in the setting of a general ward. One study reports a significant reduction in Clostridium difficile infection with the use of hospital-wide daily CHG baths.…”
Section: Introductionmentioning
confidence: 99%